#TITLE_ALTERNATIVE# - SULASTRI (NIM 20506054), SUSI
Virgin coconut oil (VCO) is an oil obtained from ripe and fresh coconut (Cocos nucifera), processed a low temperature (<600 degrees C) without bleeching or hidrogenation. VCO can be produced by enzymatic method using protease. In this research VCO exctraction was performed by dried pineapples roots for 20 hours with optimum weight ratio of powdered dried pineapples roots and coconut cream for maximum VCO rendemen. The results indicated that coconut maturity and sources of protease directly determined the VCO result. The obtained VCO has a good smell and taste, with 0,44 % water content, 0,41 acid number, 9,6 iodium number, 72,68 % lauric acid and 19,39 % myristic acid. All obtained parameters are within the range of VCO standard quality determined by APCC. The isolation of protease is carried out for characterizations. The extraction is performed in phosphate buffer pH 7, continued by fractionation by amonium sulphate and followed by dialysis. The obtained protein concentration is determined by Lowry methode, where as protease activity of fractions and crude were identified by Horikoshi methode. The result indicated that the highest activity was obtained on fraction 3 (F3) with total activities of 4,050 . 10 exponent -4 units, specific activities of 1,886 . 10 exponent -4 unit/mg, the concentration of 2,147 mg/ml, optimum pH of 8, optimum temperature of 37 0C and optimum substrate concentration (casein) is 1 %. Addition of EDTA and CaCl2 indicated that the protease is a metal protease, whereas addition of PMSF indicated that the protease is a serin protease, as PMSF decreases and even stops its activity. The SDS PAGE showed that the protease is not pure, but consist of 167,340 kDa, 151,182 kDa and 119,922 kDa of proteins.